The Improvement of Sensory Quality and Texture Properties of Gluten Free Bread Fortified with Ca - U. Krupa-Kozak; M. Wronkowska; M. Soral-Śmietana; A. Troszyńska; J. Sadowska (Czech Journal of Food Sciences, 2009)
Celiac disease is a gluten-sensitive entheropathy. Later studies suggest an increasing prevalence of that disease, likely due to the development of more sensitive methods of screening. Cereals containing prolamins such as wheat, rye, barley, and oat are toxic for celiac patients, whereas corn, rice, sorghum and buckwheat are considered to be safe. The reaction to gluten ingestion by patients suffering from that chronic disease is inflammation of the small intestine leading to the malabsorption of several important nutrients, vitamins and minerals, especially of calcium and iron. Osteopenia and osteoporosis are a frequent complication accompanying coeliac disease. The only effective treatment for coeliac disease is a long-life strict adherence to a gluten-free diet. Up to now, research studies related to gluten free bakery products have been focused on the design of gluten free matrixes by combining different starches and gluten free cereals. However, no special attention has been paid to the use of those products as carriers or vehicles of micronutrients, which are necessary for celiac patients. The aim of the research was to design of gluten free formula fortified with calcium destined to bake a bread. In that order the available organic or mineral calcium supplements were analysed. Optimisation of the technological parameters, analysis of chemical and minerals composition, sensory quality and texture of bread crumb were analysed. Preliminary estimation of bread colour, odour and taste allowed to select calcium caseinate and calcium citrate as supplements affecting beneficially the sensory quality of bread. When the mixture of both of them was applied, the improvement of bread porosity and structure was also observed. Based on the sensory evaluation of bread carried out with the method of sensory profiling and in hedonic tests gluten free bread fortified with a mixture of calcium caseinate and citrate was selected as the best. Texture properties of fresh gluten free bread crumbs fortified with calcium supplements measured using compression device of Instron were considerably improved. Summarising, the application of calcium supplements such as calcium caseinate and citrate in order to fortified gluten free bread with calcium influence beneficially its sensory and nutritional properties simultaneously enhancing the structure and texture of bread.